Nanoporous polymer foams derived from high molecular PS-b-P4VP(PDP)x for template-directed synthesis approaches. Issue 58 (31st May 2016) - Tillmann, S. D.; Hermida-Merino, D.; Winter, M.; Cekic-Laskovic, I.; Loos, K.
Abstract : Various nanoporous block copolymers derived from supramolecular complexes PS- b -P4VP(PDP) are presented as templates for template-directed synthesis approaches. Abstract : Due to their ability to self-assemble into a variety of periodic nanostructures, block copolymers already play an important role in designing diverse functional materials. A refined way to rationally tailor the morphology of a block copolymer system is the incorporation of varying amounts of an amphiphile e.g. 3-pentadecylphenol (PDP). In order to identify self-assembled structures suitable for the design of various functional materials, different supramolecular complexes of polystyrene- block -poly(4-vinylpyridine)(PDP) x (PS- b -P4VP(PDP) x ) were prepared and mophologically characterized by small-angle X-ray scattering and scanning electron microscopy techniques. Thereby, the focus was set on the cylindrical-to-lamellar region with a minor P4VP(PDP) x block. For the first time, the lamellar-in-gyroid morphology was obtained directly by an annealing process. After amphiphile removal, apart from the nanoporous gyroid polymer foam, exceptionally long-range ordered polymer networks with cylindrical pores were obtained. The manifold possible applications of the self-assembled polymer morphologies were exemplarily validated by a template-directed formation of a bicontinuous nickel network via electroless plating.